Naphthalene degradation by bacterial strain VTPG5 Isolated from oil-contaminated sediment samples collected in Baria - Vungtau - Công, Lê Thị Nhi; Mai, Cung Thị Ngọc; Huy, Vũ Ngọc; Tuân, Đỗ Văn (Vietnam Journal of Biotechnology, 2016)
Naphthalene is one of the polycylclic aromatic hydrocarbons (PAHs) which cause environmental pollution leading to mutation and cancer to human. To transform and degrade naphthalene, a number of bioremediation approaches have been investigated. The fact that bacteria can utilize naphthalene as the sole source of carbon and energy was considered as high potential method to remove naphthalene. In this research, our purpose was to find highly degrading-naphthalene bacterial strains to apply in naphthalene removal from oil-polluted sites. Three bacterial strains which could well grow on naphthalene were isolated from oil contaminated sediment samples taken from coastal zones in Baria – Vungtau province. Among them, the Rhodococcus sp. VTPG5 was demonstrated to the best aromatic hydrocarbon degrader then it was selected for further investigation. The VTPG5 strain could grow with the concentration of 200 ppm and the best concentration for degrading capacity was 150 ppm. The optimal physio-chemical conditions for growth of VTPG5 were estimated at 37oC, pH 7 and concentration of NaCl 2.5% after 7 day-incubation. Using these conditions to incubation the VTPG5, by HPLC analysis it was confirmed that 99.9 % of naphthalene was degraded by VTPG5 strain with the initial concentration of 150 ppm after 7 days. The result may lead to the use of this strain in bioremediation technology to treat naphthalene and other PAH components containing in oil-polluted sediment samples.